Contributions to the knowledge of parasitic nematodes of amphibians from the Dry Chaco ecoregion in Argentina - González, Cynthya E. (2021)
In the Argentinean Gran Chaco, numerous investigations have dealt with the diversity of vertebrates, including amphibians and reptiles. The parasitofauna of these organisms, has been more studied in some groups such as amphibians; however, from a biogeographic perspective, most of these studies were carried out in the Humid Chaco. The goal of this work is to present the nematofauna found in six species of amphibians, Rhinella diptycha, Chacophrys pierottii, Ceratophrys cranwelli, Scinax nasicus, Leptodactylus bufonius, and Odontophrynus lavillai, collected in different locations within the Dry Chaco, in the department of Matacos, Formosa, Argentina. In a total of 34 amphibians analyzed, we found 1,526 parasitic nematodes (total prevalence: 61.7%; total mean intensity: 72.6±90.3; total mean abundance: 44.9±78.9), belonging to 9 taxa: adults of Rhabdias sp., Oswaldocruzia sp., O. subauricularis, Schulzia travassosi, Aplectana hylambatis, Cosmocerca podicipinus, Oxyascaris caudacutus, Schrankiana formosula, and larvae of Physaloptera sp. These nematodes were collected from the lungs, small intestine, large intestine, gastric mucosa, and gallbladder of hosts. This work is the first record of helminths from C. pierottii and O. lavillai and the first record of nematodes from Ce. cranwelli throughout its geographical range. The species Schrankiana formosula (Atractidae) is recorded for the first time in Argentinean amphibians. Thus, we expand the knowledge of the biological diversity of helminth parasites of amphibians from the Dry Chaco ecoregion. This base-line information, would allow to understand the factors that influence the patterns of host and geographic distribution of vertebrate parasites in an area with extreme characteristics such as the Dry Chaco.